2013
DOI: 10.1111/bcpt.12037
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Administration of Infliximab (TNF‐α Inhibitor) Decreases Depression and Anxiety‐like Behaviour in Rat Model of Chronic Mild Stress

Abstract: Pro-inflammatory cytokines have been proposed to be associated with the pathogenesis of depression. Consistent with this notion, several clinical observations have suggested the antidepressant efficacy of TNF-a inhibitors in patients with chronic inflammatory diseases. In this study, we evaluated the antidepressant and anxiolytic effects of chronic TNF-a inhibitor (infliximab, 5 mg/kg, i.p., weekly) administration in the chronic mild stress (CMS) model of depression. Rats were divided into three groups: saline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
58
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(68 citation statements)
references
References 51 publications
(71 reference statements)
10
58
0
Order By: Relevance
“…For example, central administration of TNFα induced depression-like behaviors in the forced swimming test and tail suspension test (Kaster et al, 2012), while treatment with the TNFα inhibitor infliximab and targeted deletion of TNF receptors had antidepressant effects in mice (Simen et al, 2006;Karson et al, 2013). In agreement with previous studies, we found that administration of TNFα inhibitors reduced by ~20~30% the number of mice that developed learned helplessness, suggesting that stress-induced TNFα contributes to learned helplessness.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…For example, central administration of TNFα induced depression-like behaviors in the forced swimming test and tail suspension test (Kaster et al, 2012), while treatment with the TNFα inhibitor infliximab and targeted deletion of TNF receptors had antidepressant effects in mice (Simen et al, 2006;Karson et al, 2013). In agreement with previous studies, we found that administration of TNFα inhibitors reduced by ~20~30% the number of mice that developed learned helplessness, suggesting that stress-induced TNFα contributes to learned helplessness.…”
Section: Discussionsupporting
confidence: 91%
“…Administration of TNFα inhibitors tended to reduce the number of mice that developed learned helplessness, as 45% of the TNFα inhibitor-treated mice and 55% of the etanercepttreated mice exhibited learned helplessness ( Figure 9A). This supports previous reports that inhibiting TNFα exerts antidepressant properties in mouse models of depression (Karson et al, 2013;Simen et al, 2006: Kaster et al, 2012, but also demonstrates that inhibiting TNFα only modestly reduces the induction of learned helplessness depression-like behavior.…”
Section: Tlr4 −/− Mice Display Resistance To Learned Helplessness Depsupporting
confidence: 91%
“…In addition, TNF antagonism had no significant effect on study participants as a whole when not accounting for inflammatory biomarkers. These results are further supported by a study that demonstrated similar effects of Infliximab on mildly stressed rats including decreased depression and anxiety-like behavior when compared to controls and saline administration (Karson et al, 2013). All in all, these findings raise the possibility of TRD populations who could be uniquely responsive to antiinflammatory intervention, thus suggesting the need for appropriate screenings and treatment.…”
Section: Effects Of Anti-inflammatory Medications On Depressionsupporting
confidence: 63%
“…In support of this notion, infliximab was found to reduce depressive symptoms in rodent models of depression (Karson et al, 2013;Liu et al, 2015) as well as in humans suffering from major depression and exhibiting higher level of circulating CRP . Interestingly, these patients were also those who exhibited higher BMI.…”
Section: Pharmacological Strategiesmentioning
confidence: 93%